Simulation Research of the Integrated Control Strategy of Dual Clutch Transmission - Qu Xiang; Ma Anpeng; Zhang Jun; Liao Linqing (Jixie chuandong)
To improve the shifting quality of dual clutch transmission（ DCT）,the core issue of two clutches pressure control and engine speed control are studied,an integrated upshift control strategy is put forward.The simulation model of transmission system is established by using the Matlab/Simulink software,the simulation calculation of the DCT upshift under the integrated control strategy is carried out. The results show that the engine and high gear clutch speed quick synchronization can be implemented and the clutch friction work,the shift jerk can be kept in the ideal level and the shift quality of DCT vehicle is improved significantly.